Assessing Benefit Portability for International Migrant Workers : A Review of the France-Morocco Bilateral Social Security Agreement - Holzmann, Robert; Legros, Florence; Dale, Pamela (World Bank, Washington, DC, 2017)
The portability of social benefits is gaining importance given the increasing share of individuals working at least part of their life outside their home country. Bilateral social security agreements (BSSAs) are considered a crucial approach to establishing portability, but the functionality and effectiveness of these agreements have not yet been investigated; thus, importance guidance for policy makers in migrant-sending and migrant-receiving countries is missing. To shed light on how BSSAs work in practice, this document is part of a series providing information and lessons from studies of portability in four diverse but comparable migration corridors: Austria-Turkey, Germany-Turkey, Belgium-Morocco, and France-Morocco. A summary policy paper draws broader conclusions and offers overarching policy recommendations. This report looks specifically into the working of the France-Morocco corridor. Findings suggest that the BSSA between France and Morocco is broadly working well, with only a few substantive issues in the area of pensions and the task of implementing access to health care for retired migrants under the new BSSA effective as of 2011. The pension issues cluster around access to survivor’s pensions in view of civil law differences of addressing divorces and repudiation and the non-exportability of minimum pension guarantees in line with European Union legislation and lacking reciprocity. Process issues around information provision in Morocco and automation of information exchange to speed up benefit processing are recognized.